2023
DOI: 10.4028/p-20h232
|View full text |Cite
|
Sign up to set email alerts
|

The Ability of ZnFe<sub>2</sub>O<sub>4</sub> Nanostructure as Electromagnetic Wave Absorber in Frequency Range 2-18 GHz

Abstract: ZnFe2O4 nanomaterials were prepared using a solid-state reaction method using high energy milling (750 rpm) for 30 hours and calcined at 1000°C for 5 hours. The characterizations used include XRD, SEM, VSM, and VNA. The measurement results show that the sample has a single phase with a cubic structure. The surface morphology of heterogeneous samples with a particle size of 250-400 nm shows magnetic performance with Ms 2.38 emu/g and Hc 11.29 kOe. The sample also can absorb electromagnetic waves in the frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The appropriate permeability properties can work optimally at certain working frequencies so that the magnetization process will occur to dissipate the EM energy. For the range of 1–10 GHz, only a few studies reported the corresponding permeability related to this study. The effective permeability for frequencies 5 ≥ 7 ≤ 10 GHz is determined to be 2.4 ≥ 2.6 ≤ 2.9. In addition to the permeability properties, the conductive properties of materials also affect the performance of MAMs.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…The appropriate permeability properties can work optimally at certain working frequencies so that the magnetization process will occur to dissipate the EM energy. For the range of 1–10 GHz, only a few studies reported the corresponding permeability related to this study. The effective permeability for frequencies 5 ≥ 7 ≤ 10 GHz is determined to be 2.4 ≥ 2.6 ≤ 2.9. In addition to the permeability properties, the conductive properties of materials also affect the performance of MAMs.…”
Section: Resultsmentioning
confidence: 88%
“…For the range of 1–10 GHz, only a few studies reported the corresponding permeability related to this study. 93 95 The effective permeability for frequencies 5 ≥ 7 ≤ 10 GHz is determined to be 2.4 ≥ 2.6 ≤ 2.9. In addition to the permeability properties, the conductive properties of materials also affect the performance of MAMs.…”
Section: Resultsmentioning
confidence: 99%